2017
DOI: 10.4300/1949-8349.9.6s.11
|View full text |Cite
|
Sign up to set email alerts
|

Report of the SI2025 Task Force

Abstract: The "Recommendations" section concludes the report by describing ways in which the ACGME can prepare GME stakeholders for the future of health care and education in SIs with new structures and functions. § Readers are encouraged to view the components of this report as modular; that is, many sections are interrelated or self-contained, and it is not necessary to read them in a particular sequence. Some may find it useful to start with the particular findings; others may prefer to skip to the recommendations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…raduate medical education (GME) leaders continuously engage in discussions that envision the future outlook for GME and its sponsoring organizations. 1,2 For example, the GME community is now expected to explicitly link education and training to anticipated societal health care needs, 3 as articulated in the 2019 Accreditation Council for Graduate Medical Education Common Program Requirements. 4 In celebration of the Journal of Graduate Medical Education's 10th anniversary, this issue's future-oriented editorial explores what GME will look like when our journal celebrates its 20th anniversary.…”
mentioning
confidence: 99%
“…raduate medical education (GME) leaders continuously engage in discussions that envision the future outlook for GME and its sponsoring organizations. 1,2 For example, the GME community is now expected to explicitly link education and training to anticipated societal health care needs, 3 as articulated in the 2019 Accreditation Council for Graduate Medical Education Common Program Requirements. 4 In celebration of the Journal of Graduate Medical Education's 10th anniversary, this issue's future-oriented editorial explores what GME will look like when our journal celebrates its 20th anniversary.…”
mentioning
confidence: 99%
“…There is an increased emphasis on programs and sponsoring institutions designed to serve the needs of the community, incorporating social determinants of health in the educational program, resonating with growing trends and identified needs across medical education. 3,10,11 These changes have important implications for the future health care workforce of our nation. Researchers have demonstrated that differences in complication rates and costs translate from the educational setting to practice and persist decades into the future.…”
Section: Discussionmentioning
confidence: 99%
“…The ACGME has acknowledged the potential for the changing landscape of healthcare to impact residency education and as a result convened the Sponsoring Institution 2025 (SI2025) Task Force which wrote that "three forcesdemocratization, commoditization, and corporatization-were seen as drivers of change that appear to be guiding the future of healthcare, and thereby shaping the conditions to which GME and Sponsoring Institutions will need to adapt." 19 The ACGME also recognizes the importance of the sponsoring institution as demonstrated by the inclusion of hospital administrators in regular Clinical Learning Environment Review (CLER) on-site visits. The CLER Program is designed to provide hospitals and other clinical settings affiliated with the sponsoring institution with periodic feedback addressing patient safety, quality, care transitions, supervision, well-being, and professionalism.…”
Section: The Sponsoring Institutionmentioning
confidence: 99%